Analisis Status Mutu Air Sungai Berdasarkan Metode STORET Sebagai Pengendalian Kualitas Lingkungan (Studi Kasus: Dua Aliran Sungai di Kecamatan Tembilahan Hulu, Kabupaten Indragiri Hilir, Riau) - Masykur HZ; Bintal Amin; Jasril Jasril; Sofyan Husein Siregar (Dinamika Lingkungan Indonesia, 2018)
District of Tembilahan Hulu is the capital of Indragiri Hilir Regency which has two rivers, namely the Sungai Parit 11 and Sungai Parit 13. These rivers has a tidal type with the estuary on the Indragiri River. The function of these rivers is used as a rain water drainage that existence is not be separated from human activities around the watershed. Characteristics of rivers that cross urban areas are susceptible to decreasing water quality and environmental pollution from the effects of high anthropogenic activities. This study aims to analyze the status of water quality in two rivers that cross district of Tembilahan Hulu, Indragiri Regency. Sungai Parit 11 as the research area has a length of ±5 km and Sungai Parit 13 has a length of ±6 km, each of which is divided into 3 locations of sampling points representing the condition of tides and low tides. The placement of each sampling point is determined based on the representation of the upstream, middle and downstream of the river. Analysis of water quality status of the rivers is made using STORET method which comprehensive by Decree of the Minister of Environment of the Republic of Indonesia Number 115 Year 2003. The results showed the status of water quality of Sungai Parit 11 and Sungai Parit 13 in District of Tembilahan Hulu, Indragiri Hilir regency in heavily polluted conditions.